Leveraging Innovative Financing Strategy to Increase Coverage and Resources Among Informal Sector for Social Health Insurance Within the Nigerian Context of Devolution: Evidence From Adoption Model Implementation - Simeon Beluonwu Onyemaechi; Uchenna Rita Ezenwaka; Uchenna Rita Ezenwaka (Frontiers Media S.A., 2022)
BackgroundEnrollment in sub-national social health insurance schemes (SSHIS) can be challenging in developing countries like Nigeria, particularly among people in the informal sector. This could be due to a lack of knowledge on its mode of operation and benefits, distrust in government, inimical religious and traditional beliefs, as well as constraining economic factors. A complementary and innovative financing strategy such as the philanthropist adoption model (ADM) could be beneficial in improving SSHIS coverage and financial resources among persons in the informal sector. The study provides new evidence on how ADM influenced health insurance coverage and resources within SSHIS among informal settings in Nigeria. It also highlights contextual factors influencing the implementation of ADM.MethodsThis study employed a mixed-methods case-study approach undertaken in Anambra State, Southeast Nigeria. Data were collected through in-depth interviews (n = 14), document review (n = 12), and quantitative (enrollment data) methods. The respondents were purposively selected based on their involvement with the implementation of the SSHIS. Data analysis for qualitative data was done using the manual thematic framework approach while descriptive analysis was performed for the quantitative data.ResultsThe implementation of ADM was a valuable and effective strategy for improving knowledge, coverage, and resource mobilization (annual premium pool) within the SSHIS in the informal sector. The main enablers of the implementation of ADM include strong political will and commitment, wider stakeholders' consultation and collaboration, numerous public-spirited philanthropists, and legal institutionalization of health insurance. Other enablers include organizational factors like good teamwork among Anambra State Health Insurance Agency (ASHIA) staff, enabling work environment (incentives, supervision, office space), and experienced marketers in the agency. However, ADM had several barriers that affected its implementation-acceptability issues due to distrust for government and the health system, health systems barriers including substandard health facilities and equipment, and inimical cultural and religious beliefs about health insurance.ConclusionThe study demonstrates a case for the implementation of innovative ADM as a strategy for enhancing SSHIS financial sustainability and coverage of persons in the informal sector. Hence, the strategy should be adopted in settings where philanthropy abounds for increasing access to quality healthcare delivery to poor beneficiaries toward achieving universal health coverage in developing countries.